Hegemoni Media Pemberitaan Pengesahan UU KUHP Indonesia pada Media Asing - Putu Isma Saraswati; Justicia Chantika D.A; Khairunnisa Khairunnisa; Maylanny Christin (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2023)
The aim of this research is to find out the media hegemony in reporting the ratification of the Indonesian Criminal Code to foreign media. This research uses a qualitative research method in the form of a critical discourse analysis method. The research results of the four media that are the object of research have formed different discourses regarding the reporting of the Indonesian Criminal Code regarding sex before marriage according to each media ideology. In reporting, each media provides different points of view, reinforced by scientific arguments obtained from experts and critics. The conclusion of the research is that many foreign media have exercised hegemony in reporting on the ratification of the Indonesian Criminal Code Act as a mass media that opens meaning for readers to have opinions and views that agree with the government. Keywords: Criminal Code Law, Discourse Analysis, Media Hegemony,